FAKTOR-FAKTOR YANG MEMPENGARUHIKONSUMENDALAM PEMBELIANHUNIANPADAPT. ARDANGREENLANDPROPERTINDO PURWOREJO (STIE Rajawali Purworejo, 2021)
The aim of this research is to find out what factors are most dominant in consumer decisions when purchasing a house at PT. Ardan Greenland Propertindo. The population used in this research were people who bought houses at PT. Ardan Greenland Propertindo, numbering 450 people. The sampling technique used is Simple Random Sampling, namely taking sample members from the population at random without paying attention to the strata in the population. The number of samples taken in this research was 10% of the total population (450 home buyers), namely 45 home buyers. Data collection techniques in this research were obtained by observation, interviews, questionnaires, documentation and literature study techniques. Data regarding research variables was obtained through questionnaires distributed to respondents to provide responses to questions/statements in the questionnaire. The research data that has been obtained will then be analyzed using Likert scale analysis techniques with the ideal score (if all respondents choose the answer with the highest score) which is 450 and the lowest score (if all respondents choose the answer with the highest score) which is 90. The results of this research show that the factors -factors that influence purchasing decisions at PT. Ardan Greenland Propertin includes product factors, price factors, promotional factors and location factors. The results of calculating respondents' answer scores using Likert scale analysis for each factor are as follows: 1) Product factors: obtained a score of 385:450×100%=85.56%, meaning that 85.56% of respondents agree that product factors influence consumer purchasing decisions, 2) the price factor obtained a score of 395:450×100%=87.78%, meaning that 87.78% of respondents agreed that the price factor influences consumer purchasing decisions, 3) the promotion factor obtained a score of 352:450×100%=78.22%, meaning that the respondents agree that promotional factors influence consumer purchasing decisions, 4) place/environment factors obtained a score of 366:450×100%=81.33%, meaning that respondents agree that place/environment factors influence consumer purchasing decisions. From the results of the analysis carried out above, it can be seen the magnitude of the influence of each of the four existing factors, and the most dominant factor influencing PT purchasing decisions. Ardan Greenland Propertindo is a price factor. This is shown by the total score of 395 or 87.78%. From the research results, the lowest score was obtained, namely on the promotion factor, therefore the researcher gave suggestions to create advertisements on the website specifically for PT promotions. Ardan Greenland Propertindo or can make banners on the road.